2003
DOI: 10.1002/chin.200338271
|View full text |Cite
|
Sign up to set email alerts
|

“Antifreeze” Glycoproteins from Polar Fish

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 1 publication
0
52
0
2
Order By: Relevance
“…One of the antifreezing strategies is to accumulate antifreezing agents in subfreezing conditions to minimize intracellular ice formation. Natural antifreezing agents include glycerol, glucose trehalose, sorbitol, polyols in various insects (Clark and Worland, 2008;Doucet et al, 2009) and proteinaceous antifreeze molecules in polar fishes (Harding et al, 2003), insects (Clark and Worland, 2008;Doucet et al, 2009), and diatoms (Gwak et al, 2009). In laboratory environments, similar challenges were faced in the development of technologies to control biological activities in live samples by cryopreservation.…”
Section: Introductionmentioning
confidence: 98%
“…One of the antifreezing strategies is to accumulate antifreezing agents in subfreezing conditions to minimize intracellular ice formation. Natural antifreezing agents include glycerol, glucose trehalose, sorbitol, polyols in various insects (Clark and Worland, 2008;Doucet et al, 2009) and proteinaceous antifreeze molecules in polar fishes (Harding et al, 2003), insects (Clark and Worland, 2008;Doucet et al, 2009), and diatoms (Gwak et al, 2009). In laboratory environments, similar challenges were faced in the development of technologies to control biological activities in live samples by cryopreservation.…”
Section: Introductionmentioning
confidence: 98%
“…T he formation and growth of ice are highly unfavourable in most biological systems, with the exception of certain extremophiles including numerous Antarctic and Arctic fish species 1,2 . Ice formation and growth not only lead to mechanical damage on a cellular level, but also osmotic shock as the concentration of extracellular solutes rises as the liquid water volume fraction decreases 3 .…”
mentioning
confidence: 99%
“…2 Evidence shows the loss of organized ice structure at the interface as being fairly gradual, occurring over approximately 10 Å. 3 Very recently Ebbinghaus et al 7 have also questioned the previous assumption of hydrogen bonding as a dominant mechanism. By using terahertz spectroscopy they showed that antifreeze activity could be induced because the AFGP perturbs the aqueous solvent over long distances.…”
Section: Proposed Mechanism Of Antifreeze Activitymentioning
confidence: 97%